Modern construction lean project delivery and integrated practices - Forbes, Lincoln H.; Ahmed, Syed M. (Syed Mahmood) (Industrial innovation series, 2011)
"Written by Lincoln Forbes, highly regarded both for his leadership and innovation in the field of industrial engineering, this text preaches a practical approach that considers ways to improve construction processes in both traditional and lean environments. For non-lean environments, he explains how industrial engineering techniques can improve cost effectiveness and quality by optimizing at the task level. For lean environments, he provides a framework for integrating various techniques that will optimize performance to an even greater extent at the project level. These techniques enhance the use of resources to improve the quality of the built environment and with it, profitability"